Dezbatere de carte Cătălin Zamfir, România în criză, Editura Academiei Române, București, 2023 - Nicu Gavriluță; Cristina Gavriluță; Ștefan Cojocaru; Adrian Netedu; Nicoleta Ungureanu; Cristina Tofan; Sergiu Bortoș (Sociologie Românească)
The "Alexandru Ioan Cuza" University in Iasi, the Faculty of Philosophy and Social-Political Sciences, the Department of Sociology, Social Assistance and Human Resources hosted on 31st of October 2024 a book debate on the Cătălin Zamfir volume, Romania in crisis, Romanian Academy Publishing House, Bucharest, 2023. This article includes the discussions held on this scientific occasion.